Opportunities and Challenges of Public-Private Partnerships in Nepal - Nepal, Pramshu (International Research Journal of Parroha, 2024)
Public-private partnerships (PPPs) represent a strategic collaboration between the public and private sectors aimed at achieving shared objectives, particularly in the provision of public infrastructure and services. In Nepal, PPPs have emerged as a significant strategy to address the country's pressing infrastructure and service delivery challenges. This study investigates the implementation and development of PPPs in Nepal, analyzing specific projects and reviewing existing literature to identify both the benefits and challenges associated with these partnerships. The findings reveal that while PPPs have the potential to attract private investment, enhance efficiency, and promote economic growth, they face several obstacles. Key challenges include an underdeveloped legal and regulatory framework, limited government capacity, and issues related to accountability and transparency. The necessity for a clear regulatory framework is paramount, as it would provide the guidelines needed for effective collaboration between public entities and private investors. Moreover, enhancing institutional capacity and establishing robust accountability mechanisms are crucial for strengthening the PPP model in Nepal. By addressing these systemic challenges, Nepal can better leverage PPPs to improve its infrastructure, stimulate economic development, and enhance public service delivery. This study provides insights into optimizing the PPP framework in Nepal, aiming to maximize the benefits of such partnerships while mitigating associated risks.